Jerusalem and “the Jew:” Biopolitics Between Blake and Spinoza - Whitson, Roger (Romanticism on the Net)

(untitled) (Université de Montréal, 2005)
AbstractCritics exploring the relationship between Romantic poetry and Judaism have noted several places within William Blake’s poetry that seem to display philo-Semetic tendencies. This essay argues that Blake’s relationship with Jewish thought is much more complicated. It utilizes Spinoza’s understanding of the affect to rethink the contexts of Blake’s remarks about Judaism and “the Jew.” For Spinoza, the problem of the affect is a problem of reading and understanding what one is reading. This is particularly difficult, since the affects only confusedly make up what is called “the body”—whether this is a corporeal, political, or epistemological body. He applies this affectual problem of reading to his study of Biblical texts in the Theological Political Treatise, noting that Jewish law, in particular the Decalogue, only applies to the time and place of its production. Despite this, there are attempts to make a coherent message out of the Decalogue that can be transmitted outside of its spatio-temporal context. Blake has similar comments to make about the textual production of the Bible. According to Blake, the Bible is not a coherent document, and is rather made to be coherent by political bodies wishing to make a single, docile Christian identity. This paper uses these comments by Blake and Spinoza in a close reading of what is seemingly the most obvious example of Blake’s philo-semetic ideas: his address “To the Jews” in Jerusalem. I argue that whatever comments Blake makes about Jewish identity cannot be read outside of the complicated biopolitical contexts emerging from the address. Readers must fashion a disciplinary body for Blake that has philo-semetic beliefs and believe that this body pre-exists the time and space of its textual production in order to make conclusions about Blake’s relationship to Judaism. This process is precisely what Blake critiques in the essay.